Exploring the Role of HEPES Buffer in the Synthesis and Characterization of Lanthanide-Nucleotide Complexes - Santi, Santi; Amirah; Putri Salsabila, Nabila (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2024)
Lanthanide-nucleotide complexes are of interest due to their unique luminescent properties and have potential applications in a wide range of fields from medical imaging to environmental sensing. Given the sensitive nature of biochemical reactions, the choice of reaction conditions including pH plays a crucial role in determining the synthesis yield. One of the buffering agents that has gained prominence in this synthetic methodology is HEPES (4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid). This study investigates the role of HEPES buffer in maintaining stable pH conditions, which are critical for the successful formation of lanthanide-nucleotide complexes. Terbium complexes with adenosine triphosphate ligands have been successfully synthesized with a maximum reaction time of 60 minutes. The complex was characterized using a UV-Vis spectrophotometer where the absorption peak at a wavelength of 257.5 nm indicates the occurrence of π-π* electron transitions. There is an absorption band at a wavelength of 349 cm-1 in the TbATP complex using an FT-IR spectrophotometer, this can be associated with the vibration of the Tb-N bond, which confirms the formation of a terbium complex with adenosine triphosphate. A sharp infrared absorption band at a wavelength of 630 cm-1 indicates the presence of vibrations of the O-H bond bound to the terbium ion, namely the formation of a Tb-OH complex bond, indicating that the phosphate group in ATP is involved in the formation of the complex.